Collembola of Rapa Nui (Easter Island) with descriptions of five endemic cave-restricted species - Bernard, Ernest C.; Soto-Adames, Felipe N.; Wynne, J. Judson (Zootaxa, 2015)
Eight species of Collembola are reported from recent collections made in caves on the Polynesian island of Rapa Nui (Easter Island). Five of these species are new to science and apparently endemic to the island: Coecobrya aitorererere n. sp., Cyphoderus manuneru n. sp., Entomobrya manuhoko n. sp., Pseudosinella hahoteana n. sp. and Seira manukio n. sp. The Hawaiian species Lepidocyrtus olena Christiansen & Bellinger and the cosmopolitan species Folsomia candida Willem also were collected from one or more caves. Coecobrya kennethi Jordana & Baquero, recently described from Rapa Nui and identified as endemic, was collected in sympatric association with C. aitorererere n.sp. With the exception of F. candida, all species are endemic to Rapa Nui or greater Polynesia and appear to be restricted to the cave environment on Rapa Nui. A key is provided to separate Collembola species reported from Rapa Nui. We provide recommendations to aid in the conservation and management of these new Collembola, as well as the other presumed cave-restricted arthropods.